The Politics of Sport: John Day's The Isle of Gulls - Finn-Atkins, Alexandra (Early Theatre, 2024)
This article explores three scenes in John Day’s understudied satiric drama The Isle of Gulls, reading the royal hunt, game of bowls, and double jest as examples of a cultural phenomenon that disguises politics as recreation.